SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA KARYAWAN PADA KANDATEL BONE MENGGUNAKAN METODE SAW - Aulyardha Anindita; Woro Isti Rahayu (Universitas Islam Balitar, 2021)
: An employee is a person who provides services both in the form of thoughts and energy and gets compensation that has been determined by a company or an organization. In Kandatel Bone itself, the employee assessment process is still done simply by evaluating employee attendance and assessing the weekly reports of each employee so that it is still difficult in grouping data and takes a long time in validating data and potentially producing inaccurate output, and it can at any time harm employees and the company itself. So to solve the problem, a Decision Support System is needed to assess the performance of Kandatel Bone employees. Decision Support System is an interactive information system that provides information, modeling, and data manipulation commonly used for decision making in semi-structured and unstructured situations, so no one knows exactly how the decision was made. The research method used in this research is Simple Additive Weighting (SAW) method. SAW method is a method commonly known as weighted summing method by calculating the value of each alternative of the criteria, then normalizing the decision matrix, doing the sorting and determining the best employees. And design a system to be built web-based using the PHP programming language. In this study, the final questionnaire was conducted to find out user acceptance, from 23 respondents obtained the results of 89.67% of user acceptance rate. So that the results of this study showed that a Support System for Employee Performance Assessment Decisions in Kandatel Bone can be received very well by users.